2017
DOI: 10.3390/ma10080902
|View full text |Cite
|
Sign up to set email alerts
|

Hot Press as a Sustainable Direct Recycling Technique of Aluminium: Mechanical Properties and Surface Integrity

Abstract: Meltless recycling technique has been utilized to overcome the lack of primary resources, focusing on reducing the usage of energy and materials. Hot press was proposed as a novel direct recycling technique which results in astoundingly low energy usage in contrast with conventional recycling. The aim of this study is to prove the technical feasibility of this approach by characterizing the recycled samples. For this purpose, AA6061 aluminium chips were recycled by utilizing hot press process under various ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
1
30
2
1
Order By: Relevance
“…Figure 8 shows that the density has significantly increased from the lowest parameters, 60 min and 430 °C, to highest parameters, 120 min and 530 °C. Compared to the previous study by Yusuf [ 47 ], in our study the reinforcement particle increased the composite density 1.28% higher. The void-filling activities had enhanced the composite density.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Figure 8 shows that the density has significantly increased from the lowest parameters, 60 min and 430 °C, to highest parameters, 120 min and 530 °C. Compared to the previous study by Yusuf [ 47 ], in our study the reinforcement particle increased the composite density 1.28% higher. The void-filling activities had enhanced the composite density.…”
Section: Resultscontrasting
confidence: 78%
“…The increase from 71.36 to 86.66 HV 0.3 confirms that the temperature and holding time increase yielded better composite hardness. Previously, Yusuf et al [ 20 ] recorded a hardness of 81.74 HV 0.3 when aluminum chips were pressed at 530 °C with a 120-min holding time [ 47 ]. The increase of 6.02% is mostly due to the presence of Al 2 O 3 particles which reinforce and strengthen the matrix and therefore increase the hardness value.…”
Section: Resultsmentioning
confidence: 99%
“…The powder material for the matrix is produced and prepared using the recycling method from automotive component waste and beverage can package waste. The process of melting waste material uses an electric induction furnace at 700-800 0 C, and the liquid material is poured into a billet-shaped mould [36]. Afterwards, the billet products are machined by lathe and chips is crushed using a ball mill machine, and the next process is aluminium powder is sieved (mesh).…”
Section: Methodsmentioning
confidence: 99%
“…More waste generation was observed than from conventional recycling (melting), and it was also reported that primary aluminium is depleted and other resources should be utilized as alternative materials. Briefly, the hot press forging (HPF) process has been acknowledged as a promising metal forming technique that not only protects the environment but also prevents the generation of new waste [ 4 ]. Despite prior evidence that secondary aluminium production could attain superior mechanical properties, it still cannot surpass primary aluminium performance.…”
Section: Introductionmentioning
confidence: 99%